Relationship between preseason training load, match performance, and match activities in professional rugby league - Crang, Z. L.; Hewitt, A.; Scott, T. J.; Kelly, V. G.; Johnston, R. D. (The Journal of Strength and Conditioning Research, 2022)
This study aimed to establish the relationship between preseason training loads, technical match performance, and physical match activities in rugby league. Twenty-two professional rugby league players (age: 24.7 ± 4.0 years; height: 184.3 ± 4.7 cm; and body mass: 101.1 ± 9.9 kg) participated in the study. Training loads and physical match activities were monitored using global positioning systems. Total distance (m), high-speed running distance (VT1IFT; distance covered above estimated first ventilatory threshold [=68% of 30-15 intermittent fitness test]) and total session rating of perceived exertion from all field-based (32.5 ± 8.5) and gym-based sessions (39.1 ± 12.5) were used to quantify preseason loads. Physical match activities were measured as total and high-speed running distance relative to individual playing time, whereas technical match activities and performance scores were used to evaluate individual match performance. To examine the relationship between physical match activities, technical performance, and preseason load, Pearson's correlation coefficients were quantified for each in-season game before performing a Fisher Z Transformation. Preseason high-speed running distance was positively associated with high-speed match activities (r = 0.34-0.51), whereas negatively associated with technical performance scores (r = -0.51 to -0.35) and hit up m·min-1 of match-play (r = -0.30 to -0.17). It seems high speed running performed in the preseason period positively influences in-season physical match activity profiles, however, are unlikely to positively impact technical match performance.